2022
DOI: 10.1155/2022/1878766
|View full text |Cite
|
Sign up to set email alerts
|

FAM171B as a Novel Biomarker Mediates Tissue Immune Microenvironment in Pulmonary Arterial Hypertension

Abstract: The purpose of this study was to uncover potential diagnostic indicators of pulmonary arterial hypertension (PAH), evaluate the function of immune cells in the pathogenesis of the disease, and find innovative treatment targets and medicines with the potential to enhance prognosis. Gene Expression Omnibus was utilized to acquire the PAH datasets. We recognized differentially expressed genes (DEGs) and investigated their functions utilizing R software. Weighted gene coexpression network analysis, least absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Besides, several past reports confirmed our fundings. Qu et al, (2022) demonstrated that PAH might be associated with dysregulation of the immune microenvironment as well as an abnormal immune response (Qu et al, 2022). In addition, modulation of the immune microenvironment may help to slow the progression of PH .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several past reports confirmed our fundings. Qu et al, (2022) demonstrated that PAH might be associated with dysregulation of the immune microenvironment as well as an abnormal immune response (Qu et al, 2022). In addition, modulation of the immune microenvironment may help to slow the progression of PH .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several past reports confirmed our fundings. Qu et al, (2022) demonstrated that PAH might be associated with dysregulation of the immune microenvironment as well as an abnormal immune response ( Qu et al, 2022 ). In addition, modulation of the immune microenvironment may help to slow the progression of PH ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with machine learning algorithms, the cytoHubba plugin is frequently applied for the identification of key genes. On the one hand, diagnostic genes from DEIOSG were assessed using the three machine learning algorithms separately (12). After that, the intersection of the three machine learning algorithms was established.…”
Section: Screening Hub Genes By Machine Learning and Ppi Networkmentioning
confidence: 99%